Manufacturing of full-scale fibre reinforced thermoplastic composite hockey stick prototype - Tang, Mark Jian Yang (Nanyang Technological University, 2023)
Composites are an attractive material for manufacturing in a wide range of industries, providing high levels of mechanical performance at a low weight. Carbon fiber has long been the reinforcement material of choice, paired with thermosetting epoxy matrices to create the lightweight, yet strong composite parts that are attractive for use in the high-performance sporting goods industry. Ice hockey sticks have adopted the use of carbon fiber composite materials for its construction, making use of thermosetting epoxies as the resin matrix, and are conventionally manufactured through the use of fiber prepregs. An alternative manufacturing process, Bladder Assisted Resin Transfer Molding (BARTM) was trialed in this project for the manufacturing of a full-scale shaft. In addition, a novel thermoplastic resin system, Elium®, was also trialed as an alternative to traditional epoxies. Elium® has the unique property of being able to be processed at room temperature, with a short curing time, unlike other thermoplastic resins. The thermoplastic nature also affords Elium®-based composites greater ductility and damage resistance, properties that are desirable for use in sporting goods. The properties of composite sandwich structures modelled after the hockey stick blade were investigated through flat-scale trials with Elium® and compared against a selection of thermosetting epoxies representing comparable commercially available solutions. The flat-scale testing showed that Elium® composite sandwich flexural performance was lower when assembled with a PVC foam core as compared to a PMI core, with the CF/EL/PVC and CF/EL/PMI configurations reaching peak loads of 97.9 N and 217.0 N respectively. Across resin systems, Elium® had a lower flexural strength than its epoxy counterparts, with the HTEP configuration achieving 29% higher peak load and the RTEP configuration achieving 13% higher peak load for the 3 mm PMI core. Although the flexural performance of Elium® was lower than the epoxies, it still presents an attractive potential for manufacturers as it can be processed at room temperature and also has a short processing time. This grants it desirable manufacturing processing characteristics superior to its competitors, and can be attractive for applications where high strength is not critical. Through this current Final Year Project study, a new method of producing composite parts was realized which can be adopted by manufacturers for use in the mass-production of composites in a wide range of industries.